A precise mathematical approach for analyzing the performance of MIMO space–time block code systems over Weibull fading channels - Abdelmajid Bessate; Youssef Miftah; Hussain Ben-Azza; Faissal El Bouanani (EURASIP Journal on Wireless Communications and Networking, 2024)
Abstract Multiple-input–multiple-output (MIMO) systems have effectively addressed today’s high demand for 5G communications and beyond. Further, MIMO-assisted space–time block codes (STBCs) have been shown to enhance the system’s performance and provide a complete variety of coherent flat-fading channels. Additionally, the closed-form expression of the probability density function of the summation of correlated Weibull random variables remains unknown. In this work, we investigate the performance analysis of MIMO-STBC-enabled systems subject to the Weibull fading channel. New tight approximate expressions for numerous system performance metrics, e.g., outage probability, average capacity under various rate adaption methods, and average symbol/bit error rate, have been obtained. The Monte Carlo simulation method has corroborated all the presented results.